ANALISIS EFEKTIFITAS DAN KONTRIBUSI PAJAK HOTEL DAN PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA BENGKULU - Yun Fitriano; Zahrah Indah Ferina (UNIVED Press, 2021)
Yun Fitriano, Zahrah Indah Ferina; This study aims to determine the extent to which the effectiveness and contribution of hotel taxes and restaurant taxes to regional revenue (PAD) Bengkulu city. The data used in this study are secondary data on hotel taxes and restaurant taxes which are sourced from reports on the realization of the Bengkulu city regional income and expenditure budget from 2015 to 2018. The method of analysis in this study uses quantitative descriptive analysis. The results showed that the average value of the effectiveness of hotel taxes and restaurant taxes in Bengkulu City from 2015 to 2018 was quite effective, ranging from 80% to 82%. Meanwhile, the contribution of hotel tax revenue and restaurant tax from 2015 to 2018 has a very large contribution, where on average each year it has a contribution of above 4%. This shows that Bengkulu City's own revenue is influenced by a large proportion of hotel taxes and restaurant taxes. Key Words: Effectiveness, Contribution, Hotel Tax, Restaurant Tax, Original Local Government Revenue